Specific Yield Analysis of the Rooftop PV Systems Located in South-Eastern Poland - Slawomir Gulkowski (Energies, 2022)
In the last few years, Poland has experienced a significant increase in photovoltaic (PV) installations. A noticeable contribution to this dynamic growth belongs to the prosumers. This paper presents the energy efficiency analysis of nine prosumers’ PV installations located in South-Eastern Poland. Eight of the systems are grid-connected and one is a hybrid (PV with the energy storage). New technology modules with efficiencies between 19% and 21%, as well as various PV system configurations related to orientation and tilt, were taken into consideration. Final yields were found and a financial assessment was presented. The average annual specific yield of all analyzed PV systems was found to be 990.2 kWh/kWp. The highest ratio of yearly energy production was noted for the system of bifacial monocrystalline silicon modules with 20.3% efficiency (1102.9 kWh/kWp). Median and maximum yields obtained by this system for the best insolation month (June 2021) were 6.64 kWh/kWp and 7.88 kWh/kWp respectively. The annual specific yield of other systems ranged between 868.8 kWh/kWp and 1075.5 kWh/kWp in dependency on module efficiency, system orientation, or tilt angle. The amount of energy produced in the summer half-year was found to be significantly higher (between 76% and 83% depending on the system) than in the winter period. The self-consumption ratio of the energy produced by the PV system installed for company prosumers ranged from about 50% in the summer months to almost 97% in winter. The payback period was below 8 years with the levelized cost of electricity equal to 0.14 €/kWh.